2010
DOI: 10.2967/jnumed.110.076612
|View full text |Cite
|
Sign up to set email alerts
|

The Temporal Dynamics of Poststroke Neuroinflammation: A Longitudinal Diffusion Tensor Imaging–Guided PET Study with 11C-PK11195 in Acute Subcortical Stroke

Abstract: Animal experiments suggest that 2 different types of activated microglia (AMG) cells occur in the brain after a stroke: local AMG in the area of the infarct and remote AMG, which occurs along affected fiber tracts. We used 11 C-PK11195 PET to image AMG in vivo after stroke in humans in a prospective longitudinal study to investigate the temporal dynamics of AMG and relate local and remote AMG activity to pyramidal tract (PT) damage using diffusion tensor imaging (DTI). Methods: Eighteen patients underwent DTI-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
141
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(150 citation statements)
references
References 39 publications
9
141
0
Order By: Relevance
“…A more promising pathophysiological process observed in conjunction with AD pathology as well as ischemic stroke is neuroinflammation and has thus been regarded as one possible link between the 2 pathologies. 40 Recent progress in brain imaging methods, especially the combination of microglia imaging using positron emission tomography and diffusion tensor imaging using MRI, 41 has demonstrated that persisting white matter inflammation after subcortical stroke can lead to the degeneration of fiber tracts over a 6-month observation period, 42,43 which can even occur trans-synaptically in callosal fibers not directly affected by the infarct. 44 Which factors are responsible for maintaining the inflammatory response over several months remains to be investigated with vascular risk factors (hypertension, dyslipidemia, or diabetes mellitus) or genetic factors being obvious candidates.…”
Section: The Interaction Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…A more promising pathophysiological process observed in conjunction with AD pathology as well as ischemic stroke is neuroinflammation and has thus been regarded as one possible link between the 2 pathologies. 40 Recent progress in brain imaging methods, especially the combination of microglia imaging using positron emission tomography and diffusion tensor imaging using MRI, 41 has demonstrated that persisting white matter inflammation after subcortical stroke can lead to the degeneration of fiber tracts over a 6-month observation period, 42,43 which can even occur trans-synaptically in callosal fibers not directly affected by the infarct. 44 Which factors are responsible for maintaining the inflammatory response over several months remains to be investigated with vascular risk factors (hypertension, dyslipidemia, or diabetes mellitus) or genetic factors being obvious candidates.…”
Section: The Interaction Hypothesismentioning
confidence: 99%
“…Two positron emission tomographic scans were performed between 5 and 7 months after the event to assess Aβ deposition with Pittsburg B compound ( 11 C-PIB) 47 and microglia activation with 11 C-[R]-PK11195. 48 Standardized uptake value ratios for 11 C-PIB (SUVR PIB ) in global gray and white matter relative to the cerebellum 49 and uptake ratios for 11 C-[R]-PK11195 (SUVR PK ) between the stroke-affected and -unaffected hemisphere gray and white matter were analyzed. 50 The cognitive performance at 5 to 7 months after stroke (MoCA2) was negatively correlated with gray matter Aβ deposition (SUVR PIB ; Figure 2).…”
Section: The Interaction Hypothesismentioning
confidence: 99%
“…The PT delineation was based on a previously published method (Radlinska et al, 2009;Thiel et al, 2010), using the infarct region itself and cerebral peduncles as ROIs for fiber tracking. The FA ratio of the PT (rFA PT ) was calculated as a ratio of the affected and nonaffected hemisphere mean FA in the PT and NonPT groups, and as left/right hemisphere FA ratios in the TIA group.…”
Section: Fiber Tracking Of the Pyramidal Tractmentioning
confidence: 99%
“…These anterograde regions of the tract undergo Wallerian degeneration in the weeks and months after the stroke. This relationship was further investigated in a similarly-designed but longitudinal study [64] , in which the extent of anterograde microglial activity in the brainstem was found to be linearly related to the extent of pyramidal tract damage (Fig. 6).…”
Section: Microglial Activation As An Indicator Of Infl Ammationmentioning
confidence: 99%